Human rights and religiosities - Gallardo, Helio (2019)
The article exposes a socio-historical conception of human rights and shows that the link between civil society and religiosities (and especially their institutionalized forms, that is, embodied in churches, as is the case of Catholicism) has a strong pole (civil society) and a weak one (the churches). In the field of human rights, churches cannot oppose either the State or civil society. It is valid for all the States that have signed the Protocols and Pacts of Human Rights. In this way a church, for example, can reject homosexual practices in its midst, but cannot persecute or harass in any way these practices in social existence. It is not before an ethical situation but of citizen juridicity. Citizens can give themselves the sexual practices they wish while they do not constitute a crime. Religious groups can reject certain practices for their members but cannot make their rejection a political issue. A sub-theme of the article is that religious institutions and human rights are not constructively articulated spontaneously but can differ and be confronted. Keywords: Human Rights, Religiosity, Civil Society, Churches, State.